THE INCLUSION OF THE STUDENT WITH AUTISTIC SPECTRUM DISORDER IN THE CLASSROOM - Souza Monteiro, Solange Aparecida de; Marcal Ribeiro, Paulo Rennes [UNESP] (Unesp-faculdade Ciencias & Letras, 2018)
The educational inclusion of children and young people with autism spectrum disorders (ASD) has been a challenge for all those involved in the educational process, nowadays and has been the goal for educational public policies. From this theoretical essay, the objective of this article is to describe the necessary movement for the inclusion of the student with Autism spectrum disorder (ASD) in the classroom, through the characterization of the subject, from a brief analysis of the legislation, with a view to Contribute to the debate on inclusive education within the current educational model and to defend the guarantee of the participation of all in educational experiences, sharing the same spaces, living the same experiences and social relations without prejudice of any order, motivated by the difference.
Keywords: Autistic Spectrum disorder; Inclusive education; Public policy